Legal Procedures and Rules Taken by the Security Council towards Iraq’s International Problems After 2003 - Mohammed Hussain Kazem Alessawi (Journal of Legal Sciences, 2024)
The research concludes that the tagged research (the legal procedures and rules taken by the Security Council towards Iraq’s international problems after 2003), proceeded from the problem of how to distinguish between the decisions issued by the Security Council in terms of the extent of their binding and the extent of differentiation between the political assessments and the legal standards of the member states of the Security Council in the actions of the council and its decisions towards certain situations, as happened with Iraq before and after 2003. In order to answer the problem and achieve the objectives of the research 2023. We had to put forward a plan that fulfills this; the first track dealt with the definition of the Security Council and its mechanism of work to be an input to the second track, which dealt with the rules of procedure and rules of work of the Security Council and its relationship with other organs of the organization, and the third track clarified the positions of the Security Council towards Iraq as well as the Security Council resolutions concerning Iraq after 2003, through studying, analyzing and classifying these resolutions in various and varying historical epochs, in an effort by the researcher to understand the positions of the Security Council towards Iraq, and the research assumed that there is no uniform and consistent approach by the Security Council towards political changes in Iraq. In other words, the consideration and analysis of the nature of these resolutions may shed light on the nature and positions of the Security Council towards Iraq’s internal and international issues. It is important to realize that studying these resolutions and mechanisms by which they were issued in accordance with the council’s working rules may lead to positive and useful conclusions, which we may not find when the council itself is studied, because its members are diverse and different on many issues. And this difference reflected negatively or positively on the nature of the work and direction of the Security Council.